A Model for Development of Guidance for Former Thugs Based on Pioneers at Majlis Qur'an, Dhikr and Shalawat Ta'mirul Islam Surakarta - Muhammad Yasin; Sugiyo Sugiyo; Mufrod Teguh Mulyo (Journal Research of Social Science, Economics, and Management, 2022)
Human life is colored by twists and turns of problems and problems that sometimes make it difficult for humans themselves and others. They perpetuate in his word which is written in the Qur'an Karim as follows. This, of course, gives rise to the special nature of former thugs, because in their previous world not all of them wanted to carry it. Various studies to alleviate the problem of thugs have actually been carried out by the police. This means that Islamic education places morals as the main foundation before students are given other lessons. This assembly was initiated by KH. Muhammad Ali or often called Abah Ali. The education is expected to be able to form and foster good character, it is not enough to give it in schools, but the role of taklim councils is still a lot that is able to carry out learning and coaching leading to akhlakul Karimah. This research is categorized as research using a research and development (R & D) approach which begins by finding the problems that exist in the consciousness of former thugs, then proceeds to explore the results of relevant research and development problems being studied and then analyze them. The result of the research is that coaching is a process, regulation, method of fostering, and so on, or efforts, actions, and activities that are carried out efficiently. Majlis Qur'an, Dhikr, and Sholawat or commonly called Base-Cam was established around 1995, this assembly started from the call or recommendation of KH. Idris, who preached his da'wah, all leaned on the Prophet as a role model when he preached Islam.